Hubungan Status Gizi dengan Usia Menarche pada Siswi Sekolah Dasar Kelas 4, 5 dan 6 di Sekolah Dasar Negeri Grabahan Kecamatan Karangrejo Kabupaten Magetan. - Sumini Sumini (Jurnal Delima Harapan, 2014)
Public Elementary School District Grabahan Karangrejo Magetan on 5 November 2013 found the total number of 45 students. Of the 85% who are menstruating got 7 of them feel uneasy first menstrual period and 3 of them mersakan pain at first menstrual period and 5 of them have not experienced menstruasi.Dari interviewed 15 girls there that have good nutrition and malnutrition that affects their menarche , the situation can be seen from the shape of their body that looks thin and there is visible fat. The purpose of this research to determine the nutritional status of relations with the age of menarche in girls primary school grade 4, 5 and 6 at the Elementary School District Grabahan Karangrejo Magetan.This research is quantitative analytical research studies with correlational approach, this study used a form of "case-control". The population in this study schoolgirl daughter elementary school grades 4, 5 and 6, in June 2013, with the number 45, the sample in this study are all young girls of primary school grade 4, 5 and 6, the sampling technique used for sampling is saturated , the instrument used to measure nutritional status using weight scales are scales underfoot west and by the age of menarche using an interview guide. Whereas the alternative hypothesis states that there is a relationship between two variables is acceptable if the probability value at p ≤ α = 0.05 then Ho is rejected H1 with statistical test chi-square test.Most respondents with normal nutritional status (51%). Most of the respondents had experienced menarche again (71%). Based on calculations from SPSS 11.5 for Windows shows that there is a relationship with the nutritional status of menarche age, known from the results of the analysis at α = 0.05 level with a value of 0.000 Contingency Coefficient of 0.618 with a strong correlation level.Researchers hope that further improve the performance of midwives in providing counseling and management of nutritional status with age of menarche, as well as a minimum to prevent malnutrition which can inhibit their growth.